Quality Assurance Plan on a Linear Accelerator (LINAC) Plane on Nasopharynx Cancer (NFC) by using Prowess Panther 5.10 at Radiotherapy Installation Ken Saras Hospital - Pandu Kurnianto; Giner Maslebu; Jodelin Muninggar; Muhammad Hidayatullah (Advance Sustainable Science Engineering and Technology, 2023)
Radiotherapy is the treatment of cancer by using electromagnetic and particle radiation. Nasopharyngeal Cancer (NPC) is one of the difficult case to be treated in radiotherapy because its anatomical location. Precision of radiation dose is part of Quality Assurance Program as the key factor in this treatment. Thus, it is very important to ensure that the output dose of Linear Accelerator (LINAC) matched with result of Treatment Planning System (TPS). This study used Siemens LINAC Type Primus MACH Series 5633 and a set of detectors for Nasopharynx Cancer analysis with 8 field. The total dose of 5,000 cGy divided into 25 fractions with 200 cGy dose per fraction. The 8 fields are irradiated with a target on a detector device. It is then accumulated with PTW-Verisoft software by plotting the results obtained from the detector tool with PTW (phantom) which we have CT Scanned first in PTW-Verisoft. From the total detectors exposed to the radiation, the detector corresponding to PTW is 372 detectors (100%) with unsuitable detector of 0 detectors (0.00%). It is proved that the planning is 100% match for NPC with 8 fields of radiation. Thus, this method is recomended to be implemented for NPC treatment